Single Electron Memory Effect Using Random Telegraph Signals at Room Temperature - Ibukuro, Kouta; Husain, Muhammad Khaled; Li, Zuo; Hillier, Joseph; Liu, Fayong; Tomita, Isao; Tsuchiya, Yoshishige; Rutt, Harvey; Saito, Shinichi (Frontiers in Physics, 2019)
We show a manipulation of a single electron at room temperature by controlling Random Telegraph Signals (RTSs) by voltage pulses. Our silicon nanowire triple-gate transistor exhibited RTSs when potential barriers were electrically created by two of the three gates. From the statistics of the signals, we optimised the voltage pulse such that a single electron was intentionally captured in the potential well, and the retention time of approximately 10ms was observed in this memory operation. This study indicates that a single electron effect can be controllable in a form of RTSs at room temperature by electrically defining a potential well.